REPRODUCTION POSTNATAL INDUCED NEOLYMPHOGENESIS IN MODELING OF TUMOR GROWTH - R. A. Rustamkhanov; K. Sh. Gantsev; Sh. R. Kzyrgalin; A. A. Khatmullin; R. I. Garayshin; A. V. Dubrovskaya (Креативная хирургия и онкология, 2017)
In the experiment on the model of transplantable tumor models of Sarcoma M-1 neolymphogenesis process induced by tumor growth was reproduced, induced postnatal revealed lymph nodes were detected. Comparative data, defined morphological differences postnatal induced lymph nodes and normal lymph nodes were analyzed.